(untitled) (Islas, 2024)
Introduction: The need for an interdisciplinary and multidisciplinary approach in linguistic research is extensible to grammatical analysis. Adjectivation is an element, like many others, that must be analyzed within and for communicative processes. Methods: For the development of this article, theoretical and mathematical methods were used to construct a guide for the study of adjectivation, and the operationalization of this as a method of analysis is explained. The text Vino tinto y perejil by Luis Cabrera Delgado is analyzed to exemplify the phenomenon. For this purpose, the work is segmented into sections, which allows us to see the role of the adjective to solve different communicative situations according to the speaker’s intention. Results: The research showed that the syntactic position of adjectives does not always determine character. The information provided by this kind of word depends on several factors. The use of adjectives reinforces the communicative intention. Moreover, they can be used to resolve any type of communicative situation in different types of texts. Conclusions: The results of the present article justify the interdisciplinary look in the analysis of adjectivization.